Principles and practice of interventional pulmonology - Yarmus, Lonny; Herth, Felix; Ernst, Armin (Springer Nature Switzerland, 2025)
-- General Principles of Endoscopic Imaging. -- The Bronchoscope: What is Available, .-Determining Selection, and How to Properly Care for the Instrument. .-Bronchoscopy Unit Design for Advanced Procedures. .-Quality Control Mechanism for Endoscopic Procedures. .-Moderate and Deep Sedation Techniques. .-Physiology of Fixed Airway Obstruction. .-Airway Imaging -- Airway Anatomy. .-Bronchoscopy Education. .-Simulation for Endoscopy Training. .-Assessment of Vocal Cord Function and Voice Disorders. .-Conventional Biopsy Techniques. .-Bronchoalveolar Lavage. .-Cryobiopsy Technique, Training and Safety. .-Cryobiopsy for ILD. .-Radial EBUS and Real Time Sampling in the Periphery. .-Linear Endobronchial Ultrasound. .-Esophageal Ultrasound. .-Narrow Band Imaging. .-Confocal Imaging. .-Optical Coherence Tomography. .-Single Use Bronchoscopes. .-Electromagnetic Navigational Bronchoscopy. .-Transparenchchymal nodule access. .-Robotic Assisted Bronchoscopy. .-Transthoracic Needle Biopsy Techniques. .-Rapid On Site Evaluation and Specimen Preparation. .-Rigid Bronchoscopy. .-Metallic Stenting. .-Endobronchial Silicone Stents for Airway Management. .-Y-Stenting Techniques -- Montgomery T-Tubes. .-Medical Thoracoscopy/Pleuroscopy -- Pleurodesis. .-Management Principles of Empyema. .-Management of Malignant Pleural Effusions -- .-Percutaneous Tracheotomy. .-Cricothyroidotomy. .-Transtracheal Oxygen Catheter Placement and Management. .-Percutaneous Endoscopic Gastrostomy (PEG) Tube Placement -- .-Whole-Lung Lavage.